EFEKTIVITAS PROGRAM INTERVENSI SOSIAL TERHADAP PENINGKATAN KESEJAHTERAAN SOSIAL ANAK TERLANTAR DI DINAS SOSIAL KOTA MATARAM TAHUN 2025 - Annisa Dwi Ariesina; Herlina; Kholisussa'di; Rila Hardiansyah (Comm-Edu (Community Education Journal), 2026)
The problem addressed in this study is how effective the social intervention programs implemented by the Social Service Office of Mataram City are in improving the social welfare of neglected children. The purpose of this research is to assess and measure the effectiveness of these programs based on the perceptions of the children who benefit from them. The study employs a quantitative approach with a descriptive method. Data collection techniques include questionnaires, observation, and documentation, with data analysis conducted using percentage-based Likert scale interpretation. The results indicate that the social intervention programs are highly effective. Formative evaluation, which includes program relevance, implementation quality, and operational challenges, yielded a percentage score of 96.29%. Summative evaluation, which covers basic needs fulfillment, social protection, and child empowerment, achieved a score of 95,8%. The overall average effectiveness of the program is 96,05%. Therefore, it can be concluded that the social intervention programs implemented by the Social Service Office of Mataram City are highly effective in enhancing the social welfare of neglected children.